Bis(pyrazolyl)thioether/amine‐chromium(III) catalysts bearing pendant O‐ and N‐donor group for oligomerization and polymerization of ethylene. (25th January 2022) - de Oliveria, Lucilene L.; Oliboni, Robson S.; Stieler, Rafael; Casagrande, Adriana C. A.; Casagrande, Osvaldo L.
Abstract : In this work, a new family of chromium complexes supported by bis(pyrazolyl)thioether/amine ligands containing pendant O ‐ and N ‐donor groups CrCl3 S ‐bis[(3, 5‐DMPz)methyl]sulfide (2a ), CrCl3 N ‐bis[(3, 5‐DMPz)benzylamine] (2b ), CrCl3 N ‐bis[(3, 5‐DMPz)butylamine] (2c ), [CrCl2 N ‐bis[(3, 5‐DMPz)methyl][(2‐pyridinyl)methyl]amine]Cl (2d ), [CrCl2 N ‐bis[(3, 5‐DMPz)methyl][quinoline]amine]Cl (2e ), [CrCl2 N ‐bis[3, 5‐DMPz‐methyl][EtNMe2 ]amine]Cl (2f ), CrCl3 N ‐bis[(3, 5‐DMPz)methyl][2‐methoxyphenyl]amine (2g ), and CrCl3 N ‐bis[2‐(3, 5‐DMPz)methyl][(2‐pyridyl)ethyl]amine (2h ) were synthetized and characterized by elemental analysis and Fourier transform infrared spectroscopy (FTIR) spectroscopy. Density functional theory (DFT) calculations demonstrated that the pendant group as well as the spacer between the N ‐donor group and the central amine nitrogen have strong influence on the coordination motif of the ligand. Thus, 1d–1f act as tetradentate ligands while 1g and 1h preferably coordinated to the chromium metal center in a tridentate [ N, N, N ] mode fashion. The catalytic performance of 2a–2h is strongly influenced by the nature of the central bridging atom (S, N) as well as the pendant O ‐ and N ‐donor group. Upon activation with methylaluminoxane (MAO), chromium precatalysts 2a–2c, 2e, and 2f generated active systems producing oligomers ranging from C4 to C12 + with a high selectivity for α‐olefins (>82.4%). On the other hand, precatalysts bearing pyridine (2d and 2h ) and methoxy (2g ) functionalized amine bis (pyrazolyl) ligands exclusively produce polyethylene (PE) with activities in the range of 107.2–372.0 kg of PE·mol[Cr] −1 h −1 . Abstract : Cr(III) complexes supported by bis(pyrazolyl)thioether/amine ligands containing pendant O ‐ and N ‐donor groups were synthesized and their catalytic behavior in oligomerization and polymerization of ethylene has been investigated evaluating the role of the ligand, and the experimental parameters on the activity, selectivity, and product distribution. DFT calculations demonstrated that the pendant group as well as the spacer between the N ‐donor group and the central amine nitrogen have strong influence on the coordination motif of the ligand.